Palynological and palynofacies analyses of Upper Cretaceous deposits in the Haţeg Basin, southern Carpathians, Romania. (December 2019) - Ţabără, Daniel; Slimani, Hamid
Abstract: We present biostratigraphical and palaeoenvironmental analyses based on palynology and palynofacies of marine and terrestrial deposits that crop out in the central and northwestern part of the Haţeg Basin. Samples were collected from the Răchitova and Sînpetru formations. The former yielded well-preserved palynological assemblages of both terrestrial and marine origin, represented mainly by diverse spore and pollen associations, but with dinoflagellate assemblages of low diversity and low to moderate abundance. The terrestrial palynoflora is dominated by fern spores and subordinate gymnosperm and angiosperm pollen. This assemblage is indicative of a vegetation of subtropical to warm-temperate climate and suggests fluvial to coastal habitats, as well as well-drained and higher altitude areas. The Răchitova Formation is here dated as Santonian–early late Campanian, based on the dinocyst species Isabelidinium microarmum and some fern spores and early angiosperm pollen. The Sînpetru Formation, previously dated as Maastrichtian, yielded only terrestrial palynoflora, but with a low content in palynomorphs. Nevertheless, its palynological assemblage, composed of Maastrichtian pollen and spores, indicates lowland or coastal habitats and warm and humid climatic conditions, alternating with periods of arid climate. The palynofacies constituents used to reconstruct the depositional environments suggest that during the Santonian–early late Campanian, strata were laid down in an inner-outer neritic environment (with some fluctuations of water depth). This succession is followed by a deltaic to pond or lake depositions during the Maastrichtian, as indicated by the presence of large translucent phytoclasts in these deposits. A new dinocyst subspecies, Isabelidinium microarmum subsp. bicavatum, which is a distinguishable bicavate cyst, is described herein; this represents a possible key taxon for the lower to lower upper Campanian. Highlights: The Santonian–Maastrichtian palynomorphs, Haţeg basin, Romania, are studied. A new dinoflagellate cyst subspecies was identified. Paleoenvironmental conditions based on palynofacies and palynomorphs are discussed.